2010
DOI: 10.1155/2010/686480
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Cytokine Modulating Effects of Tacrolimus in Systemic Lupus Erythematosus: A Review

Abstract: Systemic lupus erythematosus (SLE) is a complex systemic autoimmune disease with involvement of both B cells and cytotoxic T lymphocytes and several cytokines aberrations. Standard therapy for SLE has its limitations. Tacrolimus, a novel calcineurin inhibitor with potent immunosuppressive effects, has been shown in the recent years to be effective in SLE therapy. This paper serves to collate the experimental and clinical data on the efficacy of tacrolimus in the treatment of SLE and lupus nephritis. Tacrolimus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…The mechanisms of action of TAC in LN have not been fully elucidated. In vitro and animal studies have shown that TAC reduces production of interleukin 2 (IL-2) and other cytokines such as tumour necrosis factor α, interferon γ, IL-6 and IL-10 by activated T cells 29. By inhibiting T cell activation, signals for B cell activation, class-switching and immunoglobulin production are indirectly attenuated 30.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of action of TAC in LN have not been fully elucidated. In vitro and animal studies have shown that TAC reduces production of interleukin 2 (IL-2) and other cytokines such as tumour necrosis factor α, interferon γ, IL-6 and IL-10 by activated T cells 29. By inhibiting T cell activation, signals for B cell activation, class-switching and immunoglobulin production are indirectly attenuated 30.…”
Section: Introductionmentioning
confidence: 99%
“…This favorable response observed in these patients of lupus suggested that tacrolimus or cyclosporine at low doses is effective in preventing lupus reactivation 152. Several recent studies have confirmed the beneficial actions of tacrolimus or FK-506, especially in the management of lupus nephritis 153,154…”
Section: Uv Radiation-induced Skin Lesions In Lupus and Mast Cellsmentioning
confidence: 90%
“…Thus, T cell functions are often modulated in the treatment of those autoimmune diseases and in suppression of rejection of transplants [13,14,15,16,17]. Since interleukin 2 (IL-2) is required to initiate and support T cell activation [18], IL-2 and IL-2 signal transduction are favorite target for T cell suppression.…”
Section: Introductionmentioning
confidence: 99%